A Plant-Centered Diet and Markers of Early Chronic Kidney Disease during Young to Middle Adulthood: Findings from the Coronary Artery Risk Development in Young Adults (CARDIA) Cohort. Issue 9 (4th June 2021) - Choi, Yuni; Steffen, Lyn M; Chu, Haitao; Duprez, Daniel A; Gallaher, Daniel D; Shikany, James M; Schreiner, Pamela J; Shroff, Gautam R; Jacobs, David R
ABSTRACT: Background: Few studies have evaluated whether plant-centered diets prevent progression of early stage chronic kidney disease (CKD). Objectives: We examined the association between plant-centered diet quality and early CKD markers. Methods: We prospectively examined 2869 black and white men and women in the Coronary Artery Risk Development in Young Adults Study free of diagnosed kidney failure in 2005–2006 [examination year 20 (Y20); mean age: 45.3 ± 3.6  y]. CKD marker changes from Y20 to 2015–2016 (Y30) were considered, including estimated glomerular filtration rate (eGFR; serum creatinine), urinary albumin-to-creatinine ratio (ACR), and both. Diet was assessed through interviewer-administered diet histories at Y0, Y7, and Y20, and plant-centered diet quality was quantified with the A Priori Diet Quality Score (APDQS). Linear regression models were used to examine the association of APDQS and subsequent 10-y changes in CKD markers. Results: After adjustment for sociodemographic, behavioral, and diet factors, we found that higher APDQS was related to less adverse changes in CKD markers in the subsequent 10-y period. Compared with the lowest APDQS quintile, the highest quintile was associated with an attenuated increase in lnACR (−0.25 mg/g; 95% CI: −0.37, −0.13 mg/g; P -trend < 0.001), whereas the highest quintile was associated with an attenuated decrease in eGFR (4.45 mL·min −1 ·1.73 m −2 ; 95% CI: 2.46, 6.43 mL·min −1 ·1.73 m −2 ). There was a 0.50 lower increase in combined CKD markers [ln(ACR) z score – eGFR z score] when comparing the extreme quintiles. Associations remained similar after further adjustment for hypertension, diabetes, and obesity as potential mediating factors. The attenuated worsening CKD marker changes associated with higher APDQS strengthened across increasing initial CKD category; those with the best diet and microalbuminuria in Y10–Y20 returned to high normal albuminuria (all P -interaction < 0.001). Conclusions: Individuals who consumed plant-centered, high-quality diets were less likely to experience deterioration of kidney function through midlife, especially among participants with initial stage characterized as mild CKD.